Construção de oficina de extensão com temas transversais: pesquisa-ação nas universidades públicas de Foz do Iguaçu - Bezerra, João Abner Santos (2025)
BEZERRA, J. A. S. (2025). Designing an Extension Workshop on Cross-Cutting Themes: An Action Research Approach in Public Universities in Foz do Iguaçu. Master's Dissertation - Postgraduate Program in Technologies, Management and Sustainability - PPGTGS, State University of Western Paraná - UNIOESTE, Foz do Iguaçu, Paraná, Brazil. Since the 1990s, cross-cutting themes such as Environmental Education, Education for Ethnic-Racial Relations, Afro-Brazilian and African History and Culture, and Human Rights have been incorporated from basic education to higher education, regulated by the Ministry of Education as criteria for evaluating undergraduate programs to contribute to students' civic education. In the university context, University Extension stands out as a tool for students to construct knowledge related to social reality. However, the implementation of these projects—cross-cutting themes and University Extension—even though encouraged in recent National Education Plans, faces challenges such as rigid curricula, resistance to innovation, administrative difficulties, and disconnection from social demands. Given this scenario, the research question emerged: How can cross-cutting themes be integrated into curricular extension activities in undergraduate programs at public universities in Foz do Iguaçu? The research aims to discuss the proposed and implemented actions during the planning and execution of three workshops that combined these elements, seeking to create spaces for discussion and action through creativity-enhancing techniques based on the social technology framework, in an interdisciplinary approach. The results demonstrate the possible integration between cross-cutting themes and extension activities, whether curricular or not. Additionally, they highlight the limitations of the workshops as a social technology and the potential of the proposed actions, which can optimize resources and promote education more aligned with social demands.